The Canterville ghost [videorecording (DVD)] - New, Giles; Self, Keiron; Wilde, Oscar, 1854-1900 (Shout! Studios, 2024)
An American family moves to England, to the infamous Canterville Chase, the ancestral home that's been haunted for 300 years by the ghost of Sir Simon de Canterville. When Sir Simon and the family's teenage daughter Virginia start plotting together to get her family back to New York, she discovers that Sir Simon has been cursed to be bound to the estate. After she uncovers the beautiful and tragic love story of Sir Simon's beloved wife, Virginia joins her new neighbor, the Duke of Cheshire, to break the curse and together with Sir Simon take down the Grim Reaper.